Resisting and Appropriating Method: Part 1 - the panel - Phillips, David J; Donovan, Gregory; Humphreys, Lee (AoIR Selected Papers of Internet Research, 2013)
Each paper in this panel explores the author’s discomfort with academic research practice. In each case and for various reasons, the author finds herself, her method, institutionalized research practice, and the field of creative inquiry enmeshed in a stultifying web of mutual resistance and dissatisfaction. Also in each case, the author regenerates creative energy by appropriating methods from less familiar and traditional realms.Method in academic knowledge practice is problematic for a variety of reasons. Methods are structures and strictures of discursive paradigms that make certain things unsayable and unseeable; they can, despite the best intentions and professional practice of the academic, reduce complexity and contingency to bland generality; they are often geared toward the production of “immutable mobiles” and the elite global circulation of subjected local knowledges.The papers in this session all seek ways out of or around, or through these problems. They hope to research in ways that produce modes of knowledge that are useful outside dominant institutions, that call on other-than-academic standards of authenticity and credibility, that fashion novel discursive frameworks to support and articulate emergent senses and phenomena, and that is playful and fun.The papers together investigate the creative possibilities of appropriating a variety of practices, including hip hop methods and ethics of remix and authorship, devised theatre techniques, ephemeral play, and mass engagement in knowledge production through hackathons and cryptoparties.